Parents receiving cancer diagnosis: emotional distress and resources to communicate with their children - Fuentes, Sònia; Blasco, Tomás (Psicooncología, 2017)
Objective: To know which resources to communicate the illness to their children and whether these resources are related with emotional distress in cancer patients at diagnosis. Method: Sixty patients aged 34-60 years, who have been recently diagnosed and had children less of 18 years old reported their resources, emotional distress and family communication style. Family communication was assessedusing the specific subscale of the FAD (McMaster Family Assessment Device). Patients resources wereassessed with a specific questionnaire whose items were valued in a 0-10 scale (being 0 nothing and 10the highest punctuation possible). Emotional distress was assessed with a numeric scale ranging 0-10.Results: Resources more available were those related with the management of daily life (mean= 8.3),followed by resources to delegate to others the care of their children. Both resources were available formore than a 80% of patients. However, resources related with telling the children the illness situation,were available to only 55% of patients. Patients with resources to communicate the illness situation totheir children reported less emotional distress. Conclusions: Parents who were recently diagnosed withcancer have more resources to manage their daily life and to delegate the care of their children to others,than to inform them about the illness and to help them to cope emotionally. Parents with less resourcesto communicate with their children show a higher level of emotional distress.
Keywords: Cancer communication; psychological resources; ill parents; sons; emotional distress